The length and content of general practice consultation in two urban districts of Beijing: a preliminary observation study. - Guanghui Jin; Yali Zhao; Chao Chen; Wenji Wang; Juan Du; Xiaoqin Lu (PLoS ONE, 2015)
Community health service center (CHSC) and community health service station (CHSS) are the main institutions where general practitioners (GPs) deliver primary care in the urban area of China. Motivated by incentive policies, visits to community health service institutions (CHSIs) increased gradually in recent years, but concerns had been raised on the quality of general practice consultation. This is a preliminary study aimed to investigate the existing problems of general practice consultation in Beijing and provide practical evidence for developing relevant policies.Six GPs from 2 CHSCs and 3 CHSSs were selected by purposive sampling. The GPs were observed for 4 or 5 consecutive days during January 2013 to March 2013. The length and content of consultations were recorded in structured observation forms. Quantitative description was applied to describe the median, percentage and frequency of variables.A total of 1135 consultations were observed. The most frequent reason for consultations was specific prescription (61.6%), followed by presenting symptoms (20.7%), check-up (9.1%), counseling (5.4%), transfusion & injection (3.0%) and sickness certificate (0.2%). The median consultation length of all consultations was 2.0 minutes. The GPs prescribed in 81.0% of the consultations, on the other hand, history taking, physical examination, explanation of illness and health education only took place in 27.0%, 28.0%, 21.9% and 17.7% of the consultations respectively.The adequacy of consultation length in CHSIs is in doubt. Most patients visited the CHSIs for prescription renewal. Health promotion e.g. health education are not adequately provided in consultations. The quality of general practice consultations was jeopardized by the large amount of patient flow for medicine renewal. Policies should be adjusted to reduce unnecessary consultations. Further studies are in need to evaluate the outcome and influencing factors of general practice consultation in China.